Human Factor's Involvement in the Consumer Protection Management - Ion Petrescu; Vasile Dinu; Camelia Ştefănescu; Eugen Dobrescu (Amfiteatru Economic Journal, 2010)
The study emphasizes the results of the excellence research dedicated to theoretical and practical basics for the human factor involvement in the consumer protection management between 2008 – 2009 at the level of National Authority for Consumer Protection, the Region Committee for Consumer Protection Sibiu, and the Brasov County Committee for Consumer Protection. The article presents several elements regarding consumer protection management and the manager's profession in the consumer protection field. In order to reflect the human factor's degree of involvement in the consumer protection management we carried out a survey at the level of National Authority for Consumer Protection (NACP). The findings of our study imply that consumer protection and its management represent a new step of human civilization, a better quality life style, implying the intensive use of information from various fields, involving the human factor not only as a producer, but also as a consumer, with a great economic and social impact. Under these circumstances, consumer protection management at the level of NACP and its local institutions is an important source of information and decision; this is not only as a way of data processing. Moreover, in order to be socially efficient visible it is necessary to imply operational and top management in fields of planning-decision, organization-coordination, training-leading and controlling-monitoring, all of them being in a special position of priority. All these allowed us to present some solutions for improving the activity of NACP, from the point of view of the human factor's involvement in this institution's management.
Keywords: D18; 330; consumer protection; human factor; consumer protection management; manager in the field of consumer protection; NACP